2021
DOI: 10.1093/eurheartj/ehab842
|View full text |Cite
|
Sign up to set email alerts
|

Immune cells in cardiac homeostasis and disease: emerging insights from novel technologies

Abstract: The increasing use of single-cell immune profiling and advanced microscopic imaging technologies has deepened our understanding of the cardiac immune system, confirming that the heart contains a broad repertoire of innate and adaptive immune cells. Leucocytes found in the healthy heart participate in essential functions to preserve cardiac homeostasis, not only by defending against pathogens but also by maintaining normal organ function. In pathophysiological conditions, cardiac inflammation is implicated in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 111 publications
0
37
0
Order By: Relevance
“…Virtually all known types of immune cells have been described within the heart of both human and rodents including monocytes/macrophages, T-cells, B-cells, natural killer (NK) cells, and mast cells. Their precise roles often are yet to be fully defined ( 74 ). A recent study showed monocytes constituted 4.3% of all cells within fetal human hearts.…”
Section: Cellular Composition Of the Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all known types of immune cells have been described within the heart of both human and rodents including monocytes/macrophages, T-cells, B-cells, natural killer (NK) cells, and mast cells. Their precise roles often are yet to be fully defined ( 74 ). A recent study showed monocytes constituted 4.3% of all cells within fetal human hearts.…”
Section: Cellular Composition Of the Heartmentioning
confidence: 99%
“…Immune cells of the adaptive immune system are the second largest cell fraction within the human heart and have been implicated with various cardiovascular diseases including myocardial infarction, myocarditis, and heart failure summarized elsewhere in a recent review by Steffens et al ( 74 ). For example, T regulatory cells (Tregs) showing elevated expression of forkhead box P3 ( FOXP3) , CD25 , cytotoxic T-lymphocyte associated protein 4 ( CTLA4) , and killer cell lectin like receptor G1 ( KLRG1) were identified during MI in mouse hearts ( 86 ).…”
Section: Cellular Composition Of the Heartmentioning
confidence: 99%
“…CCR2 + (C-C chemokine receptor + ) macrophages come from embryonic, the primary resident population in a healthy heart. However, ischemic cardiac injury induces monocyte-derived CCR2 – macrophages to infiltrate the heart ( 68 , 69 ). Engulfment results in increased fatty acid in macrophages, activate mitochondrial respiration, and initiate anti-inflammatory responses during the wound healing process ( 68 , 70 ).…”
Section: Passive Adaptionmentioning
confidence: 99%
“…Healing myocardium after ischemic injury due to infarction requires sequential recruitment of immune cells to facilitate necrotic tissue clearance and subsequent activation of mesenchymal compartment to initiate deposition of extracellular matrix resulting in formation of a collagen‐based scar tissue. Although post‐myocardial infarction (MI) leukocytosis is associated with adverse outcomes, the last two decades of investigation revealed that immune cells actively participate in tissue repair and homeostasis after MI 1 . Macrophages are the central component of the healing myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Although post‐myocardial infarction (MI) leukocytosis is associated with adverse outcomes, the last two decades of investigation revealed that immune cells actively participate in tissue repair and homeostasis after MI. 1 Macrophages are the central component of the healing myocardium. Tissue‐resident macrophages deposited during embryonic development actively maintain tissue homeostasis, but also orchestrate immune cells infiltration after ischemic injury.…”
Section: Introductionmentioning
confidence: 99%